A Decade of Fiscal Transition - Alam, Asad, 1962- 1962- (The World Bank, 2002)
Transition literature has emphasized stabilization and enterprise restructuring. Both cross-country analyses and country-specific studies have tended to focus on fiscal stabilization and its indicators, highlighting the importance of quantitative fiscal adjustment to stabilization outcomes. Less attention has been paid to the qualitative dimensions of fiscal adjustment in transition. Alam and Sundberg take stock of the extent to which fiscal adjustment has occurred during the first decade of transition in both qualitative and quantitative dimensions. They define quality as the extent to which: (1) pro-growth expenditure essential for creating future economic and social assets are maintained; (2) pro-poor expenditure, such as poverty-targeted transfers, necessary to ensure income for the poor and vulnerable are adequately provided; and (3) fiscal risks, impinging on both expenditure and revenue, are managed through transition. The authors conclude that while the quantitative magnitude of the fiscal adjustment was dramatic, the quality of this adjustment has compromised the social and economic objectives of transition, particularly in the Commonwealth of Independent States (CIS). They draw four main conclusions: - Investments in public services fell in both absolute and relative terms. - Reduced spending on government transfers contributed to a sharp increase in income inequality in the CIS. - Fiscal risks increased during the transition. - Initial conditions allowed Central European and Baltic countries to maintain higher expenditures, which may have contributed to their faster economic recovery and political support for the reforms.